2017
DOI: 10.1007/978-981-10-4451-9_2
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Women’s Empowerment in Rwanda

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Heshmati [24] depicting a negative relationship between woman's age at first marriage and women empowerment. While Brajesh and Shekhar [23] and Jeckoniah, Nombo [22] found positve relationship between woman's age at first marriage and their empowerment (decision making, work status and self-esteem).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heshmati [24] depicting a negative relationship between woman's age at first marriage and women empowerment. While Brajesh and Shekhar [23] and Jeckoniah, Nombo [22] found positve relationship between woman's age at first marriage and their empowerment (decision making, work status and self-esteem).…”
Section: Resultsmentioning
confidence: 99%
“…For assessing the determinants/sources of women empowerment, we follow the studies where the woman's age at first marriage has found positively [22,23] and negatively [24] associated with their empowerment statuses. The age of the household's head has been shown negatively related [25] and positively correlated [26] with women empowerment.…”
Section: Women Empowerment As a Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The health care empowerment factor was not significant in the groups of pregnant women and non-pregnant women without children under 5 years. Pregnant women are likely to be younger than non-pregnant women with children under 5 years, and studies have shown that younger women are less likely to be empowered than older women [ 43 ]. Non-pregnant women without children under 5 years may have less awareness of the importance of ITNs in malaria prevention because they have not attended ANC or EPI appointments, which include discussion of critical information about malaria [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result is different from the assumption, the higher the formal education level of the fisherman's wife, the lower the decision to choose the empowerment of the household business. This result differs from the empowerment of women in Rwanda who are influenced by positive and significant education background [21].…”
Section: Resultsmentioning
confidence: 59%